How Demographic Factors Impact Consumers’ Product Choice During Online Shopping : An Empirical Study of Tier-III Markets - Chincholkar, Snehal; Sonwaney, Vandana (Indian Journal of Marketing, 2022)
E-commerce is proliferating in India, and not just the tier-I cities but the tier-II and III cities are also contributing significantly to the total e-commerce sales in India. Hence, to study this upcoming market, this study tried to fill the gap in the area of the tier-III markets and product category analysis during online shopping. For this study, six tier-III cities from Maharashtra were selected, and 537 sample responses were collected from these cities in the year 2019. A questionnaire was used for data collection, and stratified random sampling technique was used to select the respondents. The collected data were analyzed using SPSS.16.0, and various statistical tests such as Cochran’s Q and crosstabulation analysis were used to conduct the analysis. The results suggested that consumers from this upcoming market engaged in online shopping, and mobile phones and related accessories and apparel and accessories were the most preferred segments for online shopping. The results also revealed that various demographic factors such as gender, age, marital status, profession, and income impacted consumers’ product choice during online shopping as for these factors p, Phi (Φ), and Cramer’s V(φc) values were reported to be significant. This research contributes to the existing literature related to online consumer buying behavior and can also help the marketers to select the right segment to design their marketing and distribution strategies specifically for the tier-III market.